Shale Oil and Gas Production Processes - Speight, James G.; Speight, James G. (Gulf Professional Publishing, 2019)
Shale Oil and Gas Production Processes delivers the basics on current production technologies and the processing and refining of shale oil. Starting with the potential of formations and then proceeding to production and completion, this foundational resource also dives into the chemical and physical nature of the precursor of oil shale, kerogen, to help users understand and optimize its properties in shale. Rounding out with reporting, in situ retorting, refining and environmental aspects, this book gives engineers and managers a strong starting point on how to manage the challenges and processes necessary for the further development of these complex resources. - Helps readers grasp current research on production from shale formations, including properties and composition - Fill in the gaps between research and practical application, including discussions of existing literature - Includes a glossary to help readers fully understand key concepts